A workbook for a course in Rizal - Fadul, Jose Arabe 1961- (C & E Publishing, Inc., 2016)
"Students of every inclination or interest-research, art, history, linguistics, literature, politics, or writing - will find something to enjoy in this compendium of creative and informative task-based lessons while learning about Rizal. Among other things, they will analyze the national hero's handwriting, translate his poems or set them to music, design Rizal stamps, visit shrines and museums, create a Rizaliana website, even learn magic tricks, and fly a kite. These innovative worksheets successfully give a new dimension to the national hero by bringing to light his little-known personality quirks, habits, viewpoints, and ideas" - cover.